Developments in the Biomechanics and Equipment of Olympic Cross-Country Skiers - Pellegrini, Barbara; Stöggl, Thomas Leonhard; Holmberg, Hans-Christer (Frontiers in Physiology, 2018)
Here, our aim was to describe the major changes in cross-country (XC) skiing in recent decades, as well as potential future developments. XC skiing has been an Olympic event since the very first Winter Games in Chamonix, France, in 1924. Over the past decades, considerable developments in skiing techniques and improvements in equipment and track preparation have increased skiing speed. In contrast to the numerous investigations on the physiological determinants of successful performance, key biomechanical factors have been less explored. Today’s XC skier must master a wide range of speeds, terrains and race distances and formats (e.g., distance races with individual start, mass-start or pursuit; knock-out and team-sprint; relays), continuously adapting by alternating between various sub-techniques. Moreover, several of the new events in which skiers compete head-to-head favour technical and tactical flexibility and encourage high-speed techniques (including more rapid development of propulsive force and higher peak forces), as well as appropriate training. Moreover, the trends towards more extensive use of double poling and skiing without grip wax in classical races have given rise to regulations in connection with Olympic distances that appear to have preserved utilization of the traditional classical sub-techniques. In conclusion, although both XC equipment and biomechanics have developed significantly in recent decades, there is clearly room for further improvement. In this context, as well for analysing performance and optimizing training, sensor technology has a potentially important role to play.